Transcriptome analysis and molecular marker discovery in Solanum incanum and S. aethiopicum, two close relatives of the common eggplant (Solanum melongena) with interest for breeding. (December 2016) - Gramazio, P.; Blanca, J.; Ziarsolo, P.; Herraiz, F.; Plazas, M.; Prohens, J.; Vilanova, S.
Abstract Background Solanum incanum is a close wild relative ofS. melongena with high contents of bioactive phenolics and drought tolerance.S. aethiopicum is a cultivated African eggplant cross-compatible withS. melongena . Despite their great interest inS. melongena breeding programs, the genomic resources for these species are scarce. Results RNA-Seq was performed with NGS from pooled RNA of young leaf, floral bud and young fruit tissues, generating more than one hundred millions raw reads per species. The transcriptomes were assembled in 83, 905 unigenes forS. incanum and in 87, 084 unigenes forS. aethiopicum with an average length of 696 and 722 bp, respectively. The unigenes were structurally and functionally annotated based on comparison with public databases by using bioinformatic tools. The single nucleotide variant calling analysis (SNPs and INDELs) was performed by mapping ourS. incanum andS. aethiopicum reads, as well as reads fromS. melongena andS. torvum available on NCBI database (National Center for Biotechnology Information), against the eggplant genome. Both intraspecific and interspecific polymorphisms were identified and subsets of molecular markers were created for all species combinations. 36 SNVs were selected for validation in theS. incanum andS. aethiopicum accessions and 96 % were correctly amplified confirming the polymorphisms. In addition, 976 and 1, 278 SSRs were identified inS. incanum andS. aethiopicum transcriptomes respectively, and a set of them were validated. Conclusions This work provides a broad insight into gene sequences and allelic variation inS. incanum andS. aethiopicum . This work is a first step toward better understanding of target genes involved in metabolic pathways relevant for eggplant breeding. The molecular markers detected in this study could be used across all the eggplant genepool, which is of interest for breeding programs as well as to perform marker-trait association and QTL analysis studies.